Button battery taping and disposal: Risk reduction strategies for the household setting. (February 2022) - Chao, Silas; Gibbs, Hannah; Rhoades, Keith; Mehrer, Christopher; Jacobs, Ian N.; Jatana, Kris R.
Abstract: Objectives: Pediatric esophageal button battery (BB) injury occurs rapidly and continues to be a significant source of morbidity and mortality. Unfortunately, a BB that no longer supplies power to a device can still have enough residual voltage to cause injury within the body. Development of additional prevention strategies for consumers may reduce esophageal injury risk. Methods: In this study, 24 commercially available button batteries (BBs) were horizontally and vertically wrapped (2 layers, full circumferential coverage, 90° apart) with 6 different types of common household tapes (Scotch®/clear, Scotch®/Magic, masking tape, packing tape/clear, packing tape/brown, black electrical tape) and left at room temperature for 30 days. In addition, 6 of the CR2032 batteries covered with each type of tape were placed in a cadaveric piglet esophageal model for a 4-h period and then compared to controls without tape for tissue pH changes and visible tissue injury. Results: None of the tape-wrapped batteries showed voltage changes nor presented any hazard stemming from BB ingestion. All 6 tape covered batteries placed in the cadaveric piglet esophageal tissue model demonstrated no visible tissue injury and no change in tissue pH in contrast to the controls. Review of BB packaging language from various brands of commercially available CR2032 batteries showed that none had specific disposal recommendations. Conclusion: Both BB and electronics manufacturers should consider instructing the use of common household tape options to cover these BB immediately after removal from a device for either recycling or disposal. Such precautions may help to reduce related ingestion injuries in children. Highlights: Button battery (BB) ingestion can cause injury rapidly. Wrapping BBs in common household tape for disposal may mitigate this risk. BBs covered in tape resulted in no injuries in cadaveric piglet esophageal models. Proper disposal of batteries is essential for injury prevention in children.